LECTURER LEARNING STRATEGIES THAT FOCUS ON DEVELOPING STUDENTS' CRITICAL THINKING: A LITERATURE REVIEW - Rita Hayati; Rusiadi Rusiadi (International Journal of Teaching and Learning, 2025)
This research aims to examine various learning strategies implemented by lecturers that focus on developing students' critical thinking. Critical thinking is an indispensable ability in the academic and professional world, as it enables individuals to analyse, assess and solve problems effectively. In this literature review, various learning methods and techniques such as group discussions, case studies, simulations, and problem-based learning are discussed as means to stimulate critical thinking. The findings of this literature review indicate that strategies that involve active student participation, constructive feedback, and an environment that supports open discussion and reflection are highly effective in developing critical thinking skills. This study also highlights the importance of the role of lecturers in creating a conducive learning atmosphere and being responsive to students' learning needs, as well as the need for training and professional development for lecturers to implement these strategies effectively. The results of this study are expected to be a reference for lecturers in designing and implementing learning strategies that can improve students' critical thinking skills.